2022
DOI: 10.3390/plants11192534
|View full text |Cite
|
Sign up to set email alerts
|

Production and Physiological Quality of Seeds of Mini Watermelon Grown in Substrates with a Saline Nutrient Solution Prepared with Reject Brine

Abstract: The economically profitable production of crops is related, among other factors, to seed quality, the production system, and the water used in irrigation or preparation of nutrient solutions. Therefore, the objective was to evaluate the phenology, production, and vigor of seeds of mini watermelons grown in saline nutrient solution and different substrates. In the fruit and seed production phase, the experiment occurred in a greenhouse with five electrical conductivities of water for nutrient solution preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…The VC content increased first, and then decreased with the decreased irrigation amount (Tables 1-4), which is consistent with the results of previous studies [8,31,37]. However, compared with other studies in a nearby area [8,24,31], it was found that under the same irrigation conditions, the quality indices, such as the TSS, SAR, and SSC, of the tomatoes in this study were better than those of the -soil grown tomatoes, which is consistent with the results of several studies [38][39][40]. Due to the different effects of a water deficit on the different yield and quality indicators, the comprehensive evaluation of different irrigation amounts in this study was conducted by utilizing the TOPISIS method.…”
Section: Discussionsupporting
confidence: 92%
“…The VC content increased first, and then decreased with the decreased irrigation amount (Tables 1-4), which is consistent with the results of previous studies [8,31,37]. However, compared with other studies in a nearby area [8,24,31], it was found that under the same irrigation conditions, the quality indices, such as the TSS, SAR, and SSC, of the tomatoes in this study were better than those of the -soil grown tomatoes, which is consistent with the results of several studies [38][39][40]. Due to the different effects of a water deficit on the different yield and quality indicators, the comprehensive evaluation of different irrigation amounts in this study was conducted by utilizing the TOPISIS method.…”
Section: Discussionsupporting
confidence: 92%